Clinopathological Profile of Acute Leukemia in Children - Harpani, PT; Parmar, BJ; Makwana, AM (Journal of Nepal Paediatric Society, 2012)
Introduction: Acute leukemia is the most common malignancy in children of which acute lymphoblastic leukemia accounts for majority of the cases. The objective of this study was to see the clinical profile, hematological parameters and assessment of response to chemotherapeutic agents in acute leukemia. This was an observational prospective study involving 58 children conducted over a period of two years from September 2005 to August 2007 at the department of paediatrics, B.J. Medical College, Ahmedabad. Materials and Methods: Leukemia was suspected in children presenting with history of prolonged fever, pallor, hepatosplenomegaly, lymphadenopathy, abnormal bleeding or history of repeated blood transfusion. A complete history, clinical examination and relevant investigations were done to diagnose leukemia. After confirmation of diagnosis, patients were treated, followed up to first remission after receiving chemotherapy. Follow up bone marrow examination was done after induction phase to confirm remission. Complete blood count and CSF cytology were done periodically during intrathecal chemotherapy. Results: Out of total 58 patients, 49 (84.5%) were ALL and 9 (15.5%) were AML. Pallor (87.9%), fever (82.7%) and fatigue (86.2%) were most common presenting symptoms. Pallor (86.2%), splenomegaly (89.6%) and hepatomegaly (84.5%) were the most common clinical signs. Forty two patients (74.2%) presented with moderate anemia. Remission was achieved in 51 cases (87.9%) after intrathecal chemotherapy. Conclusion: ALL is more common than AML in children. With detailed history and clinical examination, timely diagnosis and initiation of appropriate chemotherapy commonly leads to remission in childhood acute leukemias. J. Nepal Paediatr. Soc. 32(2) 2012 95-98 doi: http://dx.doi.org/10.3126/jnps.v32i2.6038